Exploring National-Level Determinants of Sustainability Practices in the UK Banking Sector - Echem, Kaodilichukwu Augustine; Ekemezie, Ekene (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
In recent years, sustainability has become a central concern for the global financial sector, with increasing emphasis on environmental, social, and governance (ESG) issues shaping investment decisions, risk management, and corporate strategy. This study explored national-level determinants influencing sustainability practices in the UK banking sector. Using a descriptive survey design, data were collected from 191 respondents and analyzed through mean, standard deviation, and t-test statistics. Findings showed that while respondents agreed that international agreements and financial incentives influence sustainability, they disagreed on the role of government-led initiatives, ESG integration, and public awareness. However, t-test analysis revealed no statistically significant effect of any of these factors, supporting the null hypothesis. This suggests limited influence of national-level policies and public engagement on sustainable banking practices. The results imply the need for improved regulatory frameworks, stronger government support, and better public engagement to enhance sustainability efforts across the UK banking sector. The study concludes that national policies and regulations alone are insufficient to drive sustainability in the UK banking sector. It recommends enhanced government commitment, stronger enforcement of ESG standards, and improved public engagement strategies to support sustainable finance. This research contributes to the ongoing discourse on sustainable development by highlighting gaps in national-level interventions and proposing pathways for more effective sustainability integration in the banking industry.